Mengajar Sambil Belajar di Dunia Anak Istimewa : Interpretative Phenomenological Analisys tentang Pengalaman Mengajar Guru SLB yang Tidak Memiliki Latar Belakang PLB - Shakira Ghaniya Irhamni; Syahidah Alifia; Rani Sagita; Qonita Rohima; Nahrul Izza Mutiara Aldin; Geni Novella (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
The public's perception of teaching in SLB is a difficult thing because dealing with children in SLB, but teaching in SLB is not entirely difficult if we do it sincerely. The purpose of this study was to find out the experiences faced by teachers with non-specialized backgrounds teaching ABK in special schools. This study involved three teachers with the data collection technique in this study was semi-structured interviews. This research uses an Interpretative Phenomenological Analysis (IPA) approach regarding the experiences and difficulties of teaching for teachers with non-specialist backgrounds in teaching children with special needs. There are two main themes found: (1) Description of cognitive condition, (2) Description of emotional condition. The results of this study indicate that job constraints do not worsen the working conditions of the three subjects, making them feel grateful for their careers as non-PLB teachers. These three individuals can survive with 27 their jobs because they have a sense of attachment to the SLB children, a supportive workplace, family support, and support.